2020
DOI: 10.1007/s00259-020-04978-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of [89Zr]ZrDFO-amivantamab bispecific to EGFR and c-MET for PET imaging of triple-negative breast cancer

Abstract: Background Amivantamab is a novel bispecific antibody that simultaneously targets the epidermal growth factor receptor (EGFR) and the hepatocyte growth factor receptor (HGFR/c-MET) that are overexpressed in several types of cancer including triple-negative breast cancer (TNBC). Targeting both receptors simultaneously can overcome resistance to mono-targeted therapy. The purpose of this study is to develop 89 Zr-labeled amivantamab as a potential companion diagnostic imaging agent to amivantamab therapy using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…One of the reasons for their success is that bispecific constructs targeting two receptors can help to overcome drug resistance associated with mono-targeted therapies (Thakur et al, 2018). Different bispecific imaging and/or theranostic agents have also been developed, notably the scaffolds targeting GRPR/FA and EGFR/c-MET with 99m Tc/ 177 Lu-BBN-FA (Aranda-Lara et al, 2016a;Aranda-Lara et al, 2016b) and [ 89 Zr]ZrDFOamivantamab (Cavaliere et al, 2020), respectively. These agents hold potential for clinical translation due to the high expression of targets in several molecular subtypes of breast cancer and the promise to overcome resistance to monotargeted therapy due to their multiple mechanisms of action.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the reasons for their success is that bispecific constructs targeting two receptors can help to overcome drug resistance associated with mono-targeted therapies (Thakur et al, 2018). Different bispecific imaging and/or theranostic agents have also been developed, notably the scaffolds targeting GRPR/FA and EGFR/c-MET with 99m Tc/ 177 Lu-BBN-FA (Aranda-Lara et al, 2016a;Aranda-Lara et al, 2016b) and [ 89 Zr]ZrDFOamivantamab (Cavaliere et al, 2020), respectively. These agents hold potential for clinical translation due to the high expression of targets in several molecular subtypes of breast cancer and the promise to overcome resistance to monotargeted therapy due to their multiple mechanisms of action.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Amivantamab is a new bispecific antibody with multiple mechanisms of action, including inhibition of the EGFR and the hepatocyte growth factor receptor (HGFR/c-MET) pathways (Moores et al, 2016). In a recent report it was radiolabeled with 89 Zr via a desferrioxamine chelate (DFO) to create a companion diagnostic imaging agent for this bispecific antibody (Cavaliere et al, 2020) (Bispecific antibodies, Figure 2). As overexpression of EGFR and c-MET was found in TNBC and associated with progression of the disease, the resulting [ 89 Zr]ZrDFO-amivantamab radioconjugate was evaluated in TNBC xenograft models (Cavaliere et al, 2020;Chae et al, 2016).…”
Section: Egfr/c-metmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, amivantamab is a novel bispecific antibody that simultaneously targets EGFR and the hepatocyte growth factor receptor (HGFR/c-MET) that are overexpressed in TNBC. In a recent report, Cavaliere et al [ 213 ] radiolabeled amivantamab with 89 Zr, and it demonstrated higher tumor uptake than that of the radiolabeled single-arm parent antibodies.…”
Section: Imaging Receptors In Breast Cancermentioning
confidence: 99%